2021
DOI: 10.3390/app11094119
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Patterns and Linguistic Styles for Requirements Specification: Focus on Data Entities

Abstract: Requirements specification includes technical concerns of an information system and is used throughout its life cycle. It allows for sharing the vision of the system among stakeholders and facilitates its development and operation processes. Natural languages are the most common form of requirements representation, however, they also exhibit characteristics that often introduce quality problems, such as inconsistency, incompleteness, and ambiguousness. This paper adopts the notions of linguistic pattern and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
(94 reference statements)
0
10
0
Order By: Relevance
“…This makes it more difficult and inconvenient to apply these approaches, and leads to the result that most software requirements specifications are still written in natural language in practice. The investigation of Luisa et al [9] has shown that 95% of software requirements in industry are described in natural language or controlled natural language [10,11]. In this case, it is of great significance for the methods which can assist requirements analysts to identify the defects in the natural language requirements.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it more difficult and inconvenient to apply these approaches, and leads to the result that most software requirements specifications are still written in natural language in practice. The investigation of Luisa et al [9] has shown that 95% of software requirements in industry are described in natural language or controlled natural language [10,11]. In this case, it is of great significance for the methods which can assist requirements analysts to identify the defects in the natural language requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the diversity of terms found in the literature -for instance, "syntactic requirements pattern" [1] or "requirements template" [20] -, we assume in this paper the terms "linguistic pattern" and "linguistic style", as discussed by Silva [21], to mean, respectively, the definition and the representation of such grammatical rules. In his paper, Silva focused on business-level constructs, namely on constructs like glossary terms, stakeholders, business goals, processes, events, and flows [21], and recently on data entities [22]. Although inspired by that work, this paper is substantially different because it is focused on the textual specification of use cases and use case scenarios, and discusses not only patterns and writing styles but also gathers and discusses the respective pragmatics, i.e., practical recommendations and guidelines for writing use cases and scenarios (some of them previously discussed by other authors).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, and on the contrary of other proposals, this paper supports the discussion with a unique and rich running example that includes common and pedagogical situations. This example refers to the requirements of a fictitious information system called "BillingSystem", which is an invoice management system, inspired and adapted from the example initially introduced by Silva [21], [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few papers discussed factors in the requirement negotiation process. Some papers show the gaps in the requirement negotiation process, and some papers help to find the improvements in the requirement negotiation process [81]. A list of factors of requirement negotiation is identified that need further improvement.…”
mentioning
confidence: 99%